Modelling the significance of social support, theory of planned behaviour and trust for social capital growth in energy sectors - Karunakaran V.; Shanmugam M.; Dhillon J.S.; Magalingam P. (American Institute of Physics Inc., 2023)
This study investigates the factors and theories that drive social capital in energy sector. Social capital can be procured and further developed for productive and mutual benefits, particularly for Malaysia's energy sectors with the rise of social commerce and the maturing of social media. In this study, a research framework was developed and evaluated to promote social capital. The framework defines the relationship between the Theories of Planned Behaviour (TPB) and Social Support Theory (SST) alongside Trust factors, stimulating social capital expansion in energy sectors. This research utilises PLS-SEM to examine the data gathered from employee in the energy sectors in Malaysia. The research demonstrates the presence of social capital when trust and social support exist among users and encourages positive changes and benefits in the aspects of productivity, efficiency, and profitability in energy sectors. In order to analyse the research factor's validity and its reliability, the study adapted a survey which was circulated to 100 respondents from the energy sector in Malaysia. Results show that the entire proposed factors are crucial in promoting social capital. 2022 Author(s).